Meaning Analysis of Greeting Words for Kinship In the Society of Pariaman City - Oktaviona, Alivia; Dewi, Puspita; Alawiyah, Rosidah (CV Insan Kreasi Media, 2023)
Greetings are a part of speech commonly used in everyday life. Formal and informal language can be used to greet people. Greeting words can also be used as pronouns for other people in the communication process. This part of speech is used to address someone in both singular and plural forms. This research uses a type of qualitative research using descriptive methods focuses on a phenomenological perspective to understand the meaning of events and interactions between people in Pariaman Society. The objective of this research is to identify the types of greeting words used by the Pariaman community and analyze each meaning of the greeting words. The data sources of this research originated from various sources, including informants who were born and raised in the community life of Pariaman city, various scientific papers and books. In the data collection process, this research conducted interviews and read some information from data sources, then identified and classified the data. This study found that kinship greetings in Pariaman city society are divided into three parts based on the person to be addressed, including upper ego group, parallel to the ego, and lower ego group. Gender differences also affect the different forms of greeting words used by Pariaman people.